Latent polyphenol oxidases from sago log (Metroxylon sagu): partial purification, activation, and some properties - Onsa, Galila Hassan; bin Saari, Nazamid; Selamat, Jinap; Bakar, Jamilah (American Chemical Society, 2000)
Latent polyphenol oxidase (LPPO), an enzyme responsible for the browning reaction of sago starches during processing and storage, was investigated. The enzyme was effectively extracted and partially purified from the pith using combinations of nonionic detergents. With Triton X-114 and a temperature-induced phase partitioning method, the enzyme showed a recovery of 70% and purification of 4.1-fold. Native PAGE analysis of the partially purified LPPO revealed three activity bands when stained with catechol and two bands with pyrogallol. The molecular masses of the enzymes, were estimated by SDS-PAGE to be 37, 45, and 53 kDa. The enzyme showed optimum pH values of 4.5 with 4-methylcatechol as a substrate and 7.5 with pyrogallol. The LPPO was highly reactive toward diphenols and triphenols. The activity of the enzyme was greatly enhanced in the presence of trypsin, SDS, ethanol, and linoleic acid.